Laboratory Investigation on the Compaction Properties of Lime and Fly Ash Composite - Amiralian, S; Chegenizadeh, A; Nikraz, Hamid (Planetary Scientific Research Center, 2012)
Soil stabilization has been implemented for improving soils, which have inadequate engineering properties. Chemical stabilization method is mixing additives, such as lime and fly ash with soil to modify soil characteristics. This paper describes a research that carried out to study the effects of lime and fly ash in compaction properties of sand based on the seven specimens (i.e., 1 sand, 2 lime, 2 fly ashes and 4 mixture of lime-fly ash). The effectively of lime (%1 and %2), fly ash( %5 and %10) ash and the combination of each mixture were investigated in this research study in order to evaluation the maximum dry density and optimum moisture content of sand. The given result of lime and fly ashspecimens illustrated that fly ash stabilization is more effective than lime treatment alone. However, utilization of combination of additives leads to optimum effect on compactability property of sand.